Oviposition in the bird parasitic fly Philornis torquans (Nielsen, 1913) (Diptera: Muscidae) and eggs’ adaptations to dry environments - Patitucci, Luciano Damián (2017)
The larvae of Neotropical muscid genus Philornis (Meinert, 1890) are parasites of a wide range of bird species. For a long time Philornis reproductive biology was associated with larviposition due to the low number of empirical data and studies on the life cycle of these parasitic flies. We document oviposition of a subcutaneous species, Philornis torquans (Nielsen, 1913), for first time. We provide for the first time a complete morphological description of eggs with Scanning Electric Microscopy (SEM) images and highlight some adaptations to dry environments. We found that the respiratory structure (a kind of plastron) at the anterior pole is reduced in size. This suggests that P. torquans eggs could be adapted to birds’ nests dry environment.